Membaca Kembali Akar Konflik Islam-Kristen - Arifin, Zainal (Religió: Jurnal Studi Agama-agama, 2012)
This article examines the extent of the roots of the conflict between Muslim-Christian and some new horizons full of hope about the relationship between them because both communities derived from the same ancestor, Abraham. Relationship between Islam and Christianity has been (and always) ambivalent: between conflict and peace, between harmony and discord. Qur’an, the scripture of Moslem, invites others to build an inter-religious dialogue in fair and just way. Qur’an has also put the fundamental principle such as political, economic, social and theological considerations. Since Islam and Christianity have identical sources, it is rather unproblematic to look for the equal methods and systems that could effectively found the dialogue. This article intends to discover the roots of conflict within relationship between Islam and Christianity and try to find new perspectives. This paper will discuss claim of theological finality between Islam and Christianity, Christian justification on the crusades and the efforts to build dialogue and harmony. Seeing such conditions, the world does not remind silent. It means, religious people at the International and Regional takes steps persuasive that is by holding meetings with inter-religious dialogue (inter-faith) for a discussion and find solutions of the problems that arise in the middle of cosmopolitan community by promoting the agenda of humanity, justice, and equality, and peace locally and regionally.